SIKLIS VOLTAMETRI SEL SUPERKAPASITOR DARI BIOMASSA PELEPAH SALAK - Rakhmawati Farma; Amalia Apriliani Putri; Irma Apriyani (Universitas Riau, 2022)
Snake fruit midrib (SFM) biomass has the potential to be used as a precursor material for making carbon electrodes because it has a high lignocellulosic content for supercapacitor applications. Carbon electrodes were made from snake fruit midrib biomass using a pre-carbonization process at 200 °C, chemical activation with 0.1 M KOH as an activating agent, a carbonization process with temperature variations of 500 °C, 600 °C, and 700 °C using N2 gas, and a physical activation process at 800 °C with CO2 gas. Thermogravimetric analysis shows the thermal resistance temperature of carbon powder is 317.1 °C. Analysis of the electrochemical properties of supercapacitor cells from snake fruit midrib obtained specific capacitance values of 123.23 F/g, 169.05 F/g, and 213.27 F/g for samples SFM-500, SFM-600, and SFM-700, respectively. The results showed that 700 °C was the best carbonization temperature for carbon electrodes from snake fruit midrib.